Zonulin Antagonist, Larazotide (AT1001), As an Adjuvant Treatment for Multisystem Inflammatory Syndrome in Children: A Case Series. (18th February 2022) - Yonker, Lael M.; Swank, Zoe; Gilboa, Tal; Senussi, Yasmeen; Kenyon, Victoria; Papadakis, Lena; Boribong, Brittany P.; Carroll, Ryan W.; Walt, David R.; Fasano, Alessio
Abstract : OBJECTIVES: A recent study suggests that Multisystem Inflammatory Syndrome in Children (MIS-C) is triggered by gastrointestinal breach of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) viral particles from the gut lumen into systemic circulation. The virus remains in the gut weeks to months after respiratory infection, causing zonulin release from the intestinal epithelial cells. Zonulin loosens tight junctions, permitting trafficking of highly inflammatory viral particles into circulation. Current MIS-C treatments target the subsequent immune hyperactivation, not the causative loss of mucosal barrier integrity. Larazotide, a zonulin inhibitor, prevents breakdown of tight junctions, limiting antigen trafficking. DESIGN: Children with MIS-C were treated with larazotide as an adjuvant to steroid/intravenous immunoglobulin therapy. Clinical outcomes, SARS-CoV-2 antigenemia, and cytokine profiles are reported. Outcomes were compared with children with MIS-C receiving steroids and/or IVIG therapy alone. PATIENTS: Four children with MIS-C, ages 3–17 years, were enrolled. INTERVENTIONS: Patients were treated with open label larazotide 10 mcg/kg (maximum 500 mcg/dose) orally four times daily for 21 days. MEASUREMENTS AND MAIN RESULTS: All four patients tolerated larazotide without adverse effects and displayed reduction in Spike antigenemia to undetectable levels. When compared with 22 children with MIS-C receiving steroids and/or intravenous immunoglobulin therapy alone, larazotide-treated patients reported significantly improved time to resolution of gastrointestinal symptoms ( p = 0.03), and time to clearance of Spike antigenemia ( p = 0.04), plus a trend towards shorter length of stay. CONCLUSIONS: Larazotide appears safe and well-tolerated and may offer potential benefit as an adjuvant to immune-targeted therapies. Expansion of clinical trials is urgently needed to ascertain the clinical impact of larazotide on MIS-C.